Decoding the genetics of rare disease: an interview with Monkol Lek - Monkol Lek (The Company of Biologists, 2022)
Monkol Lek, Assistant Professor at Yale University School of Medicine, and Associate Editor at Disease Models & Mechanisms, dedicates his research to finding a genetic diagnosis and improving treatments for rare disease patients. As he originally studied computer engineering at the University of New South Wales in Sydney, Australia, he now utilises computational methods to optimise large-scale genetic studies, provide globally accessible resources for genetic research communities and, importantly, resolve diagnostic odysseys for rare disease patients. Monkol completed his PhD in Prof. Kathryn North's lab at the University of Sydney, studying the genetics of muscle strength and performance, and then continued his investigation of muscle disease in Prof. Daniel MacArthur's lab at Massachusetts General Hospital and the Broad Institute. During his postdoc, he led several large-scale studies aimed at distinguishing pathogenic from benign variants, including the Exome Aggregation Consortium (ExAC) project ( Lek et al., 2016). Monkol established his own lab at Yale University School of Medicine, which continues to improve the diagnosis and treatment of rare muscle disease, and also focuses on underserved populations, whose genetic mutations are not as well characterised as those of European ancestry. In this interview, Monkol discusses how his own diagnosis with limb girdle muscular dystrophy has shaped his career and what he envisions for the future of genetic research in rare disease.